Nilai-Nilai Pendidikan Islam dalam Novel ‘Merindu Baginda Nabi’ Karya Habiburrahman El Shirazy - Suryati, Dini; Arifah, Chusna; Fitri, Sofia Ratna Awaliyah (Bestari | Jurnal Studi Pendidikan Islam, 2020)
This study aims to determine the values ​​of faith education, the values ​​of religious education, and the values ​​of moral education. The method used in this data analysis is the documentation method, the documentation method as an effort to obtain data and information in the form of written notes or images that are stored related to the problem under study. In this study the authors examined books and other sources related to the object of research, such as articles, the internet, and other books relating to the values ​​of Islamic education in the novel Merindu Baginda Nabi. In the novel Merindu Baginda Nabi, written by Habiburrahman El Shirazy, it can be concluded that: 1) The values ​​of faith education in the novel "Merindu Baginda Nabi" by Habiburrahman El Shirazy consist of: Faith in Allah SWT; Faith in Angels; Faith in the Books of Allah SWT; Faith in the Prophet Muhammad; Faith in the Last Days; and Faith in Destiny (Qada and Qadar). 2) The values ​​of religious education contained in the novel "Merindu Baginda Nabi" by Habiburrahman El Shirazy include Syahadatain (acknowledgment that there is no God but Allah and Muhammad is His Messenger); pray five times a day and night; perform Umrah and perform the pilgrimage to Baitullah. and 3) Moral education values ​​contained in the novel "Merindu Baginda Nabi" by Habiburrahman El Shirazy, among them are the Mahampang morals and the Mazmumah morals.